Coexistence of Kondo effect and Weyl semimetallic states in Mn-doped MnxVAl3 compounds. (September 2022) - Lee, Kwan-Young; Yun, Jae-Hyun; Kim, Jin Hee; Salawu, Yusuff Adeyemi; Kim, Heon-Jung; Lee, Jae Jun; Lee, Hosun; Rhyee, Jong-Soo
Abstract: The strong correlation effect in Weyl semimetal is a critical issue in condensed matter physics. Recently, the Kondo effect in Weyl semimetal was theoretically proposed but not yet experimentally realized. Here we suggest a coexistence of the Weyl semimetal and Kondo effect in disordered Mn-doped Mnx VAl3 . Dilute Mn-doping in type-II Dirac semimetal VAl3 increases the chemical potential so that Dirac point is close to the Fermi energy and lifts band degeneracy, leading to the Weyl semimetal phase transition. We observed a Kondo effect, confirmed by the resistivity minimum at T K  = 40 K, and logarithmic increase of electrical resistivity, magnetic susceptibility, and specific heat divided by temperature with a significant Sommerfeld coefficient at low temperature. The angle-resolved magnetoresistance has revealed the negative longitudinal magnetoresistance below Kondo temperature due to chiral anomaly in Mn-doped Mnx VAl3 . At low temperature below Kondo temperature (T ≤ TK ), the exchange interaction by RKKY interaction in Mnx VAl3 breaks time-reversal symmetry even in Kondo screening, resulting in the topological phase transition from Dirac to Weyl semimetal. This research shows the coexistence of the Kondo effect and Weyl semimetallic state as well as the temperature-induced topological phase transition. Graphical abstract: FIGURE Angle-resolved magnetoresistance of VAl3 at T = 2 K (a), 50 K (c) and 100 K (e), as indicated by the angle of a magnetic field from electric current direction. Angle-resolved magnetoresistance of Mn0.2 VAl3 at T = 2 K (b), 50 K (d), and 100 K (f), as indicated the angle of a magnetic field from electric current direction. Image 1 Highlights: We present the coexistence of Kondo effect in Weyl semimetal in Mnx VAl3 . We observe the topological phase transition from Dirac to Weyl semimetal. Magnetic elements doping Mn induces Kondo effect. Exchange interaction breaks time-reversal symmetry even in Kondo screening. Mn doping increases chemical potential and lifts band degeneracy leading to Weyl semimetal.